2015
DOI: 10.1080/10286020.2015.1040776
|View full text |Cite
|
Sign up to set email alerts
|

Nodulisporipyrones A–D, new bioactive α-pyrone derivatives fromNodulisporiumsp.

Abstract: Four new α-pyrone derivatives, nodulisporipyrones A-D (1-4), were isolated from the extract of an endolichenic fungal strain Nodulisporium sp. (65-12-7-1) that was fermented with rice. The structures of 1-4 were elucidated by extensive spectroscopic analysis, and the absolute configurations were determined by modified Mosher's method and electronic circular dichroism experiments. Their antimicrobial activities against Staphylococcus aureus 209P, Escherichia coli ATCC0111, Aspergillus niger R330, and Candida al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…The coupling constant 3 J H1’-H2’ = 4.0 Hz and a correlation observed between H-1’ and H-2’ in the NOESY spectrum experiment of 5 indicated that they were syn and that the relative configuration of 5 was 1’ R *,2’ S * or 1’ S *,2’ R *. The optical rotation of compound 5 , with [α] + 63 (c 1.0, MeOH), had the same sign than (1’ R ,2’ S )-LL-P880γ and (1’ R ,2’ R )-LL-P880γ and the ECD spectrum of compound 5 (Δε 281.9nm = +2.042) exhibited a positive Cotton effect at 282 nm already described for 6-(1 R , 2’ R -dihydroxyheptyl)-4-methoxy-2 H -pyran-2-one and 6-(1 R , 2’ S -dihydroxyheptyl)-4-methoxy-2 H -pyran-2-one [ 64 ]. These observations allowed the assignment of the structure and absolute configuration of 5 as the new natural product (1’ R , 2’ S )-LL-P880γ, previously described as a synthetic compound [ 69 ] and reported from Xylaria feejeenisis but without stereochemistry data [ 70 ].…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…The coupling constant 3 J H1’-H2’ = 4.0 Hz and a correlation observed between H-1’ and H-2’ in the NOESY spectrum experiment of 5 indicated that they were syn and that the relative configuration of 5 was 1’ R *,2’ S * or 1’ S *,2’ R *. The optical rotation of compound 5 , with [α] + 63 (c 1.0, MeOH), had the same sign than (1’ R ,2’ S )-LL-P880γ and (1’ R ,2’ R )-LL-P880γ and the ECD spectrum of compound 5 (Δε 281.9nm = +2.042) exhibited a positive Cotton effect at 282 nm already described for 6-(1 R , 2’ R -dihydroxyheptyl)-4-methoxy-2 H -pyran-2-one and 6-(1 R , 2’ S -dihydroxyheptyl)-4-methoxy-2 H -pyran-2-one [ 64 ]. These observations allowed the assignment of the structure and absolute configuration of 5 as the new natural product (1’ R , 2’ S )-LL-P880γ, previously described as a synthetic compound [ 69 ] and reported from Xylaria feejeenisis but without stereochemistry data [ 70 ].…”
Section: Resultsmentioning
confidence: 84%
“…Their absolute configuration has been, for most of them, deduced from diagnostic coupling constants of the H-6-H-1’-H2’ system, which we investigated in the 1 H NMR spectrum of 2 . The 3 J H-6-H-1’ ( J = 2.0 Hz) of 2 was different to that of (6 S ,1’ R ,2’ S )-nodulisporipyrone D ( 3 J H-6-H-1’ = 6.5 Hz) [ 64 ] and (6 R , 1’ S , 2’ R )-LL-P880 β ( 3 J H-6-H-1’ = 6.7 Hz) [ 65 ] but similar to that of (6 S ,1’ S ,2’ S )-LL-P880 β ( 3 J H-6-H-1’ = 1.1 Hz) [ 66 ], which indicated that the relationship between H-6 and H-1’ was syn . Moreover, the 3 J H-1’-H-2’ ( J = 6,7 Hz) of 2 was equivalent to that of (6 S ,1’ R ,2’ R )-LL-P880 β ( 3 J H-1’-H-2’ = 6.1 Hz) [ 67 ] and in the same order as that of (6 R ,1’ R ,2’ R )-LL-P880 β ( 3 J H-1’-H-2’ = 9.2 Hz) [ 67 ] and (6 S ,1’ S ,2’ S )-LL-P880 β ( 3 J H-1’-H-2’ = 9.1 Hz) [ 66 ], which identified that the relationship between H-1’ and H-2’ was anti .…”
Section: Resultsmentioning
confidence: 99%
“…These spectroscopic and structure features of α-pyrone moiety were almost identical to the reported 4-methoxy-6-subtituted α-pyrones, nodulisporipyrones B–C from fungus Nodulisporium sp. (Zhao et al, 2015). The analysis of contiguous sequence of 1 H– 1 H COSY correlations from H-7 to H-13 allowed us to establish a spin system from C-7 to C-13 belonging to a seven numbered aliphatic side-chain (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…[1] Secondary metabolites reported from this genus include polyketides, [2,3] terpenoids [4,5] and sterols. [6] Polyketides of α-pyrone derivatives are one class of the most important secondary metabolites, showing a broad spectrum of biological activities, such as cytotoxic, [7] antifungal, [8] anti-inflammatory and immunomodulatory activities. [9] As part of our continuous search for bioactive metabolites from marine invertebrates and associated fungi, [10 -13] a strain of X. feejeensis was isolated from the sponge Stylissa massa collected from the Dongsha in the South China Sea.…”
Section: Introductionmentioning
confidence: 99%